Микробиологические исследования в районе участка вечерний оазиса холмы тала (восточная Антарктида) - Мямин, В. Е.; Никитина, Л. В.; Чернявская, М. И.; Занюк, А. А.; Титок, М. А.; Лозюк, С. К.; Сидоренко, А. В.; Валентович, Л. Н.; Долгих, А. В. (Минск : БГУ, 2014)
Проведены комплексные исследования, направленные на изучение санитарно-эпидемиологической ситуации, складывающейся в районе полевой базы «Гора Вечерняя» в результате сезонной работы научно-экспедиционного отряда. Проведено выделение чистых культур и дана первичная физиолого-биохимическая характеристика бактериям, выделенным из пресноводных микроозер. Получены некоторые количественные и качественные характеристики бактериопланктона из пресноводных водоемов, а также сообществ эндолитных и гиполитных сообществ. Проведено выделение бактерий-деструкторов нефти из образцов антарктического грунта, осуществлено выделение чистых культур и идентификация 4 из 36 штаммов. = In this study, a sanitary-epidemiological quality of different water intake sources in the area of «Mount Vechernyaya» Antarctic field camp (Eastern Antarctica, Tala Hills, Enerby Land, Vecherny district) used for the needs of scientific expedition group of the 5th Belarus Antarctic Expedition (58 Russian Antarctic Expedition, field season 2012–2013) was assessed. These sources included waste-water, soil and micro-lakes that are located in the territory of the field camp. It was determined that the scientific expedition group's stay during the field season doesn't have any negative impact on the sanitary-epidemiological situation in the area of "Mount Vechernyaa" field camp. 33 bacterial strains were isolated from temporary limnetic micro-lakes with different pH values and total dissolved substances (TDS). Being isolated from different micro-lakes, these strains differ in their phenotypic features such as colony morphology and growth rate. Growth temperature range, cell morphology, type of cell wall (gram-positive or gram-negative) and catalase activity of each strain was determined. The methodology for long-time cryopreservation of Antarctic bacterial strains was optimized. Further studies are necessary for molecular genetic identification of isolated bacteria and their enzymatic activity determination.